Modeling the interaction of Jupiter's magnetospheric plasma ions with satellite - Khelemelia, O.V.; Fomina, A.P.; Novak, O.P.; Kholodov, R.I. (Problems of Atomic Science and Technology, 2023)
Jupiter’s moons are constantly bombarded by ions produced by the giant planet’s plasma magnetosphere. The influence is considered as one of the main sources of the moons’ atmosphere and surface modification. This investigation is an attempt to explore the interaction of space ions with Ganymede’s magnetosphere. Computer simulations are performed using electromagnetic fields that are close to experimentally observed fields in previous Jupiter space missions. Супутники Юпітера постійно бомбардуються іонами плазми гігантської магнітосфери планети. Цей вплив вважається одним з основних джерел модифікації атмосфери і поверхні супутників. Дане дослідження є спробою вивчити взаємодію іонів плазми з магнітосферою Ганімеда за допомогою комп’ютерного моделювання, при цьому використ о вуються значення електромагнітних полів з даних попередніх космічних місій до Юпітера.